2021
DOI: 10.3390/ma14040838
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Microstructure and Mechanical Properties of CNTs-AlSi10Mg Composites Fabricated by Selective Laser Melting

Abstract: CNT-AlSi10Mg composites fabricated by SLM have drawn a lot attention in structural application due to its excellent strength, elasticity and thermal conductivities. A planetary ball milling method was used to prepare the carbon nanotube (CNT)-AlSi10Mg powders, and the CNT-AlSi10Mg composites were fabricated by selective laser melting (SLM). The density, microstructure and mechanical properties of CNT-AlSi10Mg composites were studied. The density of the test samples increased at first and then decreased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…The alloy’s microstructure consists of a cell-like Al matrix (dark phase) and a fibrous eutectic silicon grid (light phase). Thus, the main reason for the occurrence of fibrous Si is the rapid solidification during SLM [ 14 ]. Inside the molten pool, cell-like dendrites grow toward the center of the molten pool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alloy’s microstructure consists of a cell-like Al matrix (dark phase) and a fibrous eutectic silicon grid (light phase). Thus, the main reason for the occurrence of fibrous Si is the rapid solidification during SLM [ 14 ]. Inside the molten pool, cell-like dendrites grow toward the center of the molten pool.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is much research on preparing AlSi10Mg alloys by adding nanoparticles, such as LaB 6 [ 12 ], CNTs [ 13 , 14 ], GNPs [ 15 ], TiC [ 16 ], TiB 2 [ 17 ], SiC [ 18 ], Al 2 O 3 [ 19 ], AlN [ 20 ], BN [ 21 ], and TiN [ 22 ], to improve mechanical properties. Tan et al [ 12 ] used an edge-to-edge model (E2EM) to study the crystallographic match between Al and other nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al noted that Orowan looping was a possible strengthening mechanism for CNT modified AlSi10Mg due to the presence of nanoscale eutectic silicon particles, precipitated silicon particles, and Al 4 C 3 on partially reacted CNTs [50]. Luo et al explored the use of CNTs to modify AlSi10Mg components fabricated by AM techniques and determined that the main strengthening mechanisms were grain refinement strengthening, secondary phase strengthening, where the structure acts as a pinning point to inhibit dislocation motion, causing the dislocations to bend between nanostructures, causing stresses that prevent any subsequent motion of dislocations, and load transfer strengthening [62]. Phase strengthening is made possible by the presence of nanoscale eutectic silicon precipitates in the aluminum and the CNTs' outer wall coated with Al 4 C 3 .…”
Section: Carbon Nanotube and Graphene Platelet Reinforcementmentioning
confidence: 99%
“…These structures strengthen the aluminum matrix and subsequently improve overall strength. Further, the addition of CNTs to AlSi10Mg promoted the formation of Al 4 C 3 on the outer surfaces of the CNTs, which improved the interface stability and worked to enhance load transfer strengthening [62]. Wang et al explored the fabrication of CNT modified AlSi10Mg and noted enhanced strength characteristics.…”
Section: Carbon Nanotube and Graphene Platelet Reinforcementmentioning
confidence: 99%
“…Due to differences in local microstructure, it has been reported that the loading behaviors of AlSi10Mg tensile test samples cut from a single SLM part are significantly dependent on their loading directions with respect to the building direction, [2] the building height [10] and geometries [11] of the sampling locations. Enormous studies have focused on process parameters, including laser scan strategy, [12,13] scan speed, [14] construction angles, [2,15] and hatch spacing [16] to optimize the printed sample's microstructures, especially the morphology and distribution of Si-rich phase and pores. But until now, there has been no standard applicable to the SLM printing processes.…”
Section: Introductionmentioning
confidence: 99%